The Influence of Health Workers’ Knowledge, Attitudes and Compliance on Implementation of Standard Precautions in Hospital-Acquired Infections Prevention at X Hospital Bantul - Permana, Muhammad Ade Bagus; Hidayah, Nur (Archives of Business Research, 2018)
Prevention of infection is a form of efforts to maintain patient safety in health services in hospitals. However, the large number of health workers with low knowledge, inappropriate attitudes and non-adherence in the implementation of standard precautions makes increase the number of infections acquired in hospitals. This was an observational analytic study with cross-sectional design. Knowing the knowledge, attitudes and compliance to 99 health workers consisting of nurses and midwives in the inpatient room, intensive care unit and delivery room of X Hospital Bantul during July to August 2017. Data analysis using multiple logistic regression. There are three things that are assessed are knowledge, attitude and obedience. All aspects are assessed to have an effect on the application of standard precautions where compliance is the most influential factor in the application of standard precautions in the prevention of hospital-acquired infections.